Zero- and minimal fluoroscopic approaches during ablation of supraventricular tachycardias: A systematic review and meta-analysis. (19th May 2022) - Debreceni, D; Janosi, K; Vamosi, M; Komocsi, A; Simor, T; Kupo, P
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Catheter ablations for cardiac arrhythmias are conventionally performed under fluoroscopic guidance. Using three dimensional electroanatomical mapping systems to guide these procedures, zero/minimal fluoroscopy (Z/MF) approaches became available. Purpose: Our aim was to conduct a meta-analysis comparing these two different methods for the treatment of paroxysmal supraventricular tachycardias (SVT). Methods: Electronic databases were searched and systematically reviewed for studies comparing procedural parameters and outcomes of conventional, fluoroscopy-guided vs. Z/MF approaches in patients undergoing EP procedures for SVTs. The random-effects model was used to derive mean difference (MD) and risk ratios (RR) with 95÷ confidence interval (CI). Results: 24 studies involving 9, 074 patients met our inclusion criteria. There were no differences between the groups in acute success (RR=1.00, 95÷ CI, 0.99–1.01; p=0.97) and long-term success rate (RR: 1.01, 95÷ CI, 1.00–1.03; p=0.13). Compared to the conventional method, Z/MF ablation significantly reduced fluoroscopic time (MD: -10.95 min (95÷ CI, -18.43 to -3.46 min; p<0.01)) and ablation time (MD: -25.23 s (95÷ CI: -42.04 to -8.43 s; p<0.01)). Procedure time (MD: 3.06 min (95÷ CI: -0.97 to 7.08; p=0.14)) and number of ablation applications (MD: 0.13 (95÷ CI: -0.86 to 1.11; p=0.80)) were not different between the groups. Complication rate was 1.59% in the entire study population and did not differ among the groups (RR: 0.68, 95÷ CI: 0.45–1.05; p=0.08). Conclusions: Z/MF approach for the catheter ablation of SVTs is a feasible method that reduces radiation exposure and ablation time but does not compromise the acute and long-term success, or complication rates.